Cultivating famine: data, experimentation and food security, 1795–1848 - Lidwell-Durnin, J (Cambridge University Press, 2020)
Collecting seeds and specimens was an integral aspect of botany and natural history in the eighteenth century. Historians have until recently paid less attention to the importance of collecting, trading and compiling knowledge of their cultivation, but knowing how to grow and maintain plants free from disease was crucial to agricultural and botanical projects. This is particularly true in the case of food security. At the close of the eighteenth century, European diets (particularly among the poor) began shifting from wheat- to potato-dependence. In Britain and Ireland during these decades, extensive crop damage was caused by diseases like ‘curl’ and ‘dry rot’ – leading many agriculturists and journal editors to begin collecting data on potato cultivation in order to answer practical questions about the causes of disease and methods that might mitigate or even eliminate their appearance. Citizens not only produced the bulk of these data, but also used agricultural print culture and participation in surveys to shape and direct the interpretation of these data. This article explores this forgotten scientific ambition to harness agricultural citizen science in order to bring stability and renewed vitality to the potato plant and its cultivation. I argue that while many agriculturists did recognize that reliance upon the potato brought with it unique threats to the food supplies of Britain and Ireland, their views on this threat were wholly determined by the belief that the diseases attacking potato plants in Europe had largely been produced or encouraged by erroneous cultivation methods.